Degradation Kinetics of Ascorbic Acid in Xanthan Gum Solution - Runqi JIA; Yujie TANG; Weiwei HE; Xiaoxiao SONG; Junyi YIN (Shipin gongye ke-ji, 2025)
Ascorbic acid (AA) reacts with polysaccharides, resulting in changes in the rheological and structural properties of the polysaccharides. However, the degradation characteristics of AA and its degradation kinetics during this reaction require further investigation. In this study, xanthan gum (XG), a highly viscous and stable polysaccharide, was employed as the polysaccharide base for the construction of a simulation system. The changes of AA in XG solutions were investigated under varying substrate concentrations, reaction temperatures, and reaction conditions, including the addition of H2O2 or metal ions (Fe2+ and Cu2+). The results showed that the degradation of AA within XG solution surpassed that in pure water. Particularly, the degradation rate of AA, which was originally 7.03% in the absence of XG, increased to 11.72% when 0.2%XG (w/v) was present in the system at a concentration of 1 mmol/L. In addition, elevated reaction temperature accelerated the reaction between AA and XG, leading to a degradation rate of AA increased to 45.59% after heating at 90 ℃for 1 h. The degradation process of AA in this system followed the second-order reaction kinetics equation. The presence of H2O2 and metal ions (Fe2+ and Cu2+) notably accelerated AA degradation, whereas the XG solution system attenuated the degradation impact of metal ions on AA. It was found that the degradation of AA by metal ions and XG was antagonistic. In conclusion, thermal treatment of AA in pure water induced its degradation, with the addition of XG, H2O2, and metal ions (Fe2+ and Cu2+) significantly affected the degradation rate of AA. These findings hold significance for the regulation of AA degradation in food processing contexts.